MEK inhibitors beyond monotherapy: current and future development. (August 2015) - E Templeton, Ian; Musib, Luna
Highlights: Combination BRAFi/MEKi resulted in improved survival in BRAFV600E/K patients. Mutations leading to BRAFi and MEKi resistance have been observed. MEKi class toxicities include ocular (RVO) and cardiac toxicity (LVEF). Complex MEKi resistance mechanisms support investigation of novel drug combinations. Abstract : The development of MEK inhibitors has led to improved progression-free survival in patients with mutant BRAF V600 cancers when used in combination with BRAF inhibitors. However, resistance to combination therapy remains an issue. This review summarizes our current understanding of the role of MEK in cancer cell proliferation and the mechanisms which lead to resistance in patients. Specific adverse events, which have been linked to the MEK inhibitor class, have been described. Future combinations of MEK inhibitors with other cancer therapy options, currently under investigation in clinical trials, are also discussed.